Financial resilience of British SMEs during the financial crisis of 2008 - To, Le Anh Nguyet (Journal of Finance - Marketing Research, 2023)
Access to finance is considered one of the top constraints on SMEs’ growth and survival. During bank crises, although facing a credit crunch, a few SMEs still survive, hence I study what makes survivor SMEs’ financial resilience. This is not clearly defined in previous studies. The study contributes to these with empirical evidence of SMEs in the UK from pre- to post-crisis of the bank crisis of 2008. The study finds that the financial resilience of the SMEs is affected positively by a supplier network, profitability, internal equity, and diversity of financing, but negatively by bank loan dependence. During the crisis, the key driving factor for SMEs’ financial resilience is profitability. It remains a challenge for policymakers to offer a stable financing strategy to assist SMEs.